2015
DOI: 10.3341/kjo.2015.29.6.382
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Serum Cortisol and Testosterone Levels in Acute and Chronic Central Serous Chorioretinopathy

Abstract: PurposeTo compare the levels of serum cortisol and testosterone in acute and chronic central serous chorio-retinopathy (CSC).MethodsSerum cortisol and testosterone levels in 30 patients with either acute or chronic CSC were evaluated using chemiluminescent immunoassay.ResultsThe mean age was 42.43 ± 6.37 years (range, 32 to 56 years). The mean 8:00 to 9.00 a.m. serum cortisol level was 12.61 ± 4.74 µg/dL (range, 6.58 to 27.42 µg/dL). The mean serum testosterone level was 5.88 ± 1.57 ng/dL (range, 2.81 to 9.94 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 31 publications
1
12
2
Order By: Relevance
“…14 On the contrary, some other studies had found no relation between increased cortisol level as well as serum testosterone level and chronic CSCR. 15,16 There exists controversy regarding the role of corticosteroids and the pathogenesis of CSCR. On one hand, steroids are said to strengthen the tight junctions and reduce bloodbrain and blood-retinal barrier breakdown, and also lowers permeability of vessels.…”
Section: Discussionmentioning
confidence: 99%
“…14 On the contrary, some other studies had found no relation between increased cortisol level as well as serum testosterone level and chronic CSCR. 15,16 There exists controversy regarding the role of corticosteroids and the pathogenesis of CSCR. On one hand, steroids are said to strengthen the tight junctions and reduce bloodbrain and blood-retinal barrier breakdown, and also lowers permeability of vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, concentrations of steroid hormones, such as cortisol, aldosterone, and testosterone, have been widely investigated in patients with CSC; however, the findings have not been consistent, showing associations in some studies but not in others [6][7][8][9][10][11][12][13][14][15][16]. Serotonin (5-hydroxytryptamine (5-HT)), a neurotransmitter, influences many brain functions and plays important roles in the gastrointestinal system, blood, and brain, affecting behavior and physiology [17].…”
Section: Introductionmentioning
confidence: 99%
“…Serum levels of testosterone have not been shown to be elevated in CSCR. [4][5][6] However, there are case reports of exogenous testosterone use in association with CSCR in men and women. [7][8][9][10] Testosterone supplementation has become increasingly popular, despite some controversy regarding the risks and benefits.…”
Section: Introductionmentioning
confidence: 99%